Deformation-Induced Interfacial Interaction in Elastically-Plastically Deformed Single Crystals of CdxHg₁₋xTe - Koman, B.P. (Металлофизика и новейшие технологии, 2017)
In this paper, features of deformation-induced interfacial interaction in uniaxial loaded crystals and its contribution to the formation of a stressedly plastic state are analysed.